2020
DOI: 10.1684/epd.2020.1209
|View full text |Cite
|
Sign up to set email alerts
|

Are Sub‐Saharan epileptic people less photosensitive? A Senegalese study of photoparoxysmal response in a reference epilepsy centre*

Abstract: The photoparoxysmal response (PPR) is defined as the occurrence of generalized spike, spike-wave or polyspike-wave discharges consistently elicited by intermittent photic stimulation (IPS). PPR is not well studied in Sub-Saharan African people. We prospectively studied the epidemiological, clinical, and EEG characteristics of PPR among consecutive patients recorded at the clinical neurophysiology unit of Fann University Hospital (Dakar, Senegal). Methods. Among 6,808 EEG recordings including 3,065 pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Studies of ethnic origin and photosensitivity have not been conclusive, but several studies suggest a lower prevalence in Black Sub-Saharan Africans compared with their White counterparts. 113 Prevalence PPR studies documented the highest values in adolescents. 125 A very recent study evaluating PPR prevalence based on a scored database of 10,671 EEG studies confirmed this prevalence.…”
Section: Photosensitivity In Individuals Without Epilepsymentioning
confidence: 96%
See 4 more Smart Citations
“…Studies of ethnic origin and photosensitivity have not been conclusive, but several studies suggest a lower prevalence in Black Sub-Saharan Africans compared with their White counterparts. 113 Prevalence PPR studies documented the highest values in adolescents. 125 A very recent study evaluating PPR prevalence based on a scored database of 10,671 EEG studies confirmed this prevalence.…”
Section: Photosensitivity In Individuals Without Epilepsymentioning
confidence: 96%
“…123 Black Africans are less likely than Caucasians to have visually sensitive seizures. 113 The prognosis of visually sensitive seizures is fair but not great, with a 14%-37% probability of remission. Photosensitivity results from both genetic and environmental factors, but genetics are especially important.…”
Section: Needsmentioning
confidence: 99%
See 3 more Smart Citations